2003
DOI: 10.1063/1.1566468
|View full text |Cite
|
Sign up to set email alerts
|

Unusual increase of the Auger recombination current in 1.3 μm GaInNAs quantum-well lasers under high pressure

Abstract: Single-mode quantum cascade lasers employing asymmetric Mach-Zehnder interferometer type cavities Appl. Phys. Lett. 101, 161115 (2012) Bistability patterns and nonlinear switching with very high contrast ratio in a 1550nm quantum dash semiconductor laser Appl. Phys. Lett. 101, 161117 (2012) Relative intensity noise of a quantum well transistor laser Appl. Phys. Lett. 101, 151118 (2012) Blue monolithic AlInN-based vertical cavity surface emitting laser diode on free-standing GaN substrate Appl. Phys. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…2). Several mechanisms could contribute to this phenomenon, for example, a less efficient in-well absorption of the pump (the overall reflectivity of the structure at the pump wavelength increases from 20% at 10 C to 45% at 90 C), an increase in the Auger recombination [16], or hole leakage [17].…”
Section: Vcselmentioning
confidence: 98%
“…2). Several mechanisms could contribute to this phenomenon, for example, a less efficient in-well absorption of the pump (the overall reflectivity of the structure at the pump wavelength increases from 20% at 10 C to 45% at 90 C), an increase in the Auger recombination [16], or hole leakage [17].…”
Section: Vcselmentioning
confidence: 98%
“…The devices were positioned in a spring clip in a piston-in-cylinder high pressure system as described elsewhere. 9 The lasers were driven by a pulsed source with 500-ns-long pulses at a repetition rate of 10 kHz to avoid internal heating. A set of 1.5-mm-long ascleaved InGaAs/ InP laser diodes emitting at 1.5 m was investigated.…”
mentioning
confidence: 99%
“…If 0 a a > , then it is called tensile strain and if 0 a a < , then it is called compressive strain. The analytical expression for strain in the perpendicular direction is [6] are Luttinger parameters. For calculating the conduction sub-bands and valence sub-bands of the quantum well region of a VCSEL, the well known time independent Schrodinger's equation [9] has been used.…”
Section: Computation Of Energy Sub-bands In the Quantum Wellsmentioning
confidence: 99%
“…It has been found that the defect-related nonradiative recombination is significantly high in InGaAsN material due to the difficulty in the growth of high quality nitride compounds [6].…”
Section: Introductionmentioning
confidence: 99%